Using The SMART Method For Web-Based Employee Performance Measurement - Apriani, Rika; Dwita, Febrisi; Sumardiono, Sumardiono; Sabil, Muhammad Ramsa (Gema Wiralodra, 2024)
Employee performance appraisal is one of the important aspects in human resource management that serves to measure individual contributions to the organization. At Matahari Departement Store (MDS) Cileungsi, the performance appraisal process is still done manually which takes time and is often subjective. This research aims to implement the SMART (Simple Multi-Attribute Rating Technique) method in a decision support system (DSS) to improve the efficiency and objectivity of employee performance appraisals using system development in the form of RAD (Rapid Application Development). The SMART method was chosen for its ability to combine various assessment criteria with adjustable weights. The implementation of this method involves several stages, including identification of assessment criteria, determination of weights, data collection, and calculation of final scores. The results show that the developed system can provide a more structured and transparent employee performance appraisal than the manual method. This system is expected to help the management of MDS Cileungsi in making more informed decisions regarding employee development